Understanding thioamitide biosynthesis using pathway engineering and untargeted metabolomics. Issue 20 (26th April 2021) - Eyles, Tom H.; Vior, Natalia M.; Lacret, Rodney; Truman, Andrew W.
Abstract : Heterologous expression, pathway mutations and detailed metabolomic analysis were used to deduce a model for the biosynthesis of thiostreptamide S4, which belongs the thioamitide family of antitumour RiPPs. Abstract : Thiostreptamide S4 is a thioamitide, a family of promising antitumour ribosomally synthesised and post-translationally modified peptides (RiPPs). The thioamitides are one of the most structurally complex RiPP families, yet very few thioamitide biosynthetic steps have been elucidated, even though the biosynthetic gene clusters (BGCs) of multiple thioamitides have been identified. We hypothesised that engineering the thiostreptamide S4 BGC in a heterologous host could provide insights into its biosynthesis when coupled with untargeted metabolomics and targeted mutations of the precursor peptide. Modified BGCs were constructed, and in-depth metabolomics enabled a detailed understanding of the biosynthetic pathway to thiostreptamide S4, including the identification of a protein critical for amino acid dehydration that has homology to HopA1, an effector protein used by a plant pathogen to aid infection. We use this biosynthetic understanding to bioinformatically identify diverse RiPP-like BGCs, paving the way for future RiPP discovery and engineering.